Age-related differences in ocular biometry in adult Korean population. Issue 1 (December 2016) - Kim, Jung-Hoon; Kim, Moosang; Lee, Seung-Jun; Han, Sang; Kong, Young; Yang, Hee; Hyon, Joon
Abstract Background To evaluate the relationship between age, axial length (AL), anterior chamber depth (ACD) and corneal steepness (K) in patients with cataract. Methods In this retrospective study, medical records of 800 patients (800 eyes) who were diagnosed with cataract and received preoperative ophthalmologic examination were reviewed. Data including age, gender and ocular biometric data including AL, ACD and K were collected and analyzed using univariate and multivariate analyses. Results Univariate analysis showed increased age has significant correlation with shorter AL (P < 0.001), shallower ACD (P < 0.001) and steeper K (P < 0.001).K value has a negative correlation with AL (P < 0.001). In multivariate analysis, increasing age has a significant association with shorter AL (P < 0.001) and ACD (P < 0.001), although the association between age and K was not significant (P = 0.398). Negative correlation between AL and K remained significant in multivariate analysis (P < 0.001). Conclusion In patients with cataract, older age had significant association with shorter AL and ACD. AL and K had negative correlation.